Perancangan Sistem Informasi Agenda Bulanan Kantor Pencarian Dan Pertolongan Kelas A Medan Berbasis Visual Basic - Yahfizham; Febry Pratama; Ali Nafia Nasution (CV. ITTC INDONESIA, 2024)
The monthly agenda information system is an integral part of the effective management of organizational activities such as the Medan Class A Search and Rescue Office. The purpose of this study is to plan and execute a Visual Basic-based information system that can facilitate the management of monthly agendas, attendance recording, and the creation of activity reports. Research and development is the research methodology employed, with stages including needs analysis and system design, implementation, and evaluation. The result is a desktop-based application that allows admins and staff to easily create, edit, and delete agendas, as well as record the attendance of event participants. The system also provides an automatic notification feature about activities that are close to implementation. The system's evaluation reveals that the use of Visual Basic is able to produce an intuitive and functional interface for users. Overall, It is anticipated that the installation of this system will boost productivity and transparency in the management of the monthly agenda, making a beneficial addition to the operations of the Search and Rescue Office.